Bridging the gap: Contributions of academics and national security practitioners to counterterrorism in Indonesia - Sukabdi, Zora A. (International journal of law, crime and justice, 2021)
The revision of the Anti-Terrorism Law in Indonesia stimulates ongoing discussions about collaboration of all instruments of counterterrorism, coordination, and the important role of both academics and practitioners in the field. This study aims to identify variety of contributions of academics and national security practitioners to counterterrorism in Indonesia. Participants from government agencies and universities working on terrorism were involved in the study. Moreover, the study administered systematic review and qualitative text analysis to documents of CVE (Counter Violent Extremism). The findings demonstrate that there are fifteen aspects addressed in counterterrorism in which academics and practitioners are working simultaneously. Moreover, there are similarities and differences of contributions by academics and national security practitioners in each of these fifteen aspects of counterterrorism.